Komponen Penentu Biaya dalam Penetapan Freight Cost Di PT Global Marine Jakarta - Indriyani; Frilia Esti Anggraeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2019)
This study aims to analyze the factors that influence the freight cost and the percentage of selling to buying at PT. Global Marine in the freight forwarding division. This type of research is a qualitative descriptive study which is a description of a company's secondary sources which is a study that does not make calculations. The results of this study show that PT. Global Marine spends a number of different freight costs on each job adjusted for distance, needs, and port of delivery as well as the percentage between selling and buying at that company. The costs incurred by the company can be concluded that there are trucking costs, lift off / on, loading freight, seal fees, handling, ocean freight, doc fee + 10% vat, telex reales, forklifts, cleaning, storage, labor, THC, collateral containers, amendment fee, document, custom, mechanical, udername, and import insurance. While the percentage difference between seling and buying is seen from the comparison between selling and profit per job.